2018
DOI: 10.1111/fcre.12335
|View full text |Cite
|
Sign up to set email alerts
|

Considering Destructive Interparental Conflict and Intimate Partner Abuse: Is there a Difference?

Abstract: Building on existing evidence that destructive interparental conflict and intimate partner abuse (IPA) share research methodology and predict the same adjustment difficulties across numerous areas of child development, this article brings awareness to differences in terminology across disciplines and the impact these nuanced differences may have on families. We begin by identifying two main streams of scholarships followed by a discussion of research methodology similarities and differences. Important implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Rather than couple conflict more generally, here we focus on hostile destructive conflict , characterized by physical and verbal aggression, hostility, and threats (Cummings & Davies, 2002). Mounting evidence points to the negative consequences of destructive conflict, including poor marital functioning (Birditt et al, 2010), compromised parenting (Kopystynska et al, 2020), and negative developmental outcomes for children (Kopystynska & Beck, 2018).…”
Section: Conceptual Framework and Choice Of Study Constructsmentioning
confidence: 99%
“…Rather than couple conflict more generally, here we focus on hostile destructive conflict , characterized by physical and verbal aggression, hostility, and threats (Cummings & Davies, 2002). Mounting evidence points to the negative consequences of destructive conflict, including poor marital functioning (Birditt et al, 2010), compromised parenting (Kopystynska et al, 2020), and negative developmental outcomes for children (Kopystynska & Beck, 2018).…”
Section: Conceptual Framework and Choice Of Study Constructsmentioning
confidence: 99%
“…Perhaps unsurprisingly, given that high‐conflict divorces have been linked to adverse child outcomes (Haddad et al, ; Kopystynska & Beck, ), almost all of the participants reported that their children were negatively impacted by the custody‐related challenges that the families experienced. Several participants also specifically pointed to the lack of affirmation of a child's asserted gender—by ex‐partners and, in some cases, mandated by the courts—as a source of children's distress.…”
Section: Discussionmentioning
confidence: 99%
“…Much work on IPC has been in reference to interparental hostility and aggression. These studies suggest that children's exposure to such behaviors places them at risk for a host of psychological and behavioral problems, thus outlining the direct effect of IPC on child development (Davies et al, 2006;Kopystynska & Beck, 2018). As active recipients of their environment, children learn to model behaviors, both positive and negative, by observing their early socializing agentstheir parents (Bandura, 1977).…”
Section: Introductionmentioning
confidence: 99%